Lower extremity vein digital photoplethysmography in highly qualified football players and wrestlers - Sophromadze, Z.; Chabashvili, N.; Kakhabrishvili, Z. (Georgian Medical News, 2006)
Modern sport, along with the high technical, tactic and psychological readiness, requires good physical preparation achieved by a big physical load during trainings and competitions. Aim of the investigations was to study lower extremity venous system functional condition during physical load in highly qualified football players and wrestlers. Highly qualified 25 football players and 30 wrestlers, of age 18-25 years, were studied. Olympic, World and Europe champions were included among wrestlers. Lower extremity venous system digital photopletismography (D-PPG) was conducted by apparatus: Rheo Dopplex II of Huntleight Diagnostics. The equipment digitally analyses photopletismoghraphic plots. Significant functional parameters: vein restoration time (VRT) and venous pump function (VP) in deep venous system were reported by the apparatus appropriate software. It included parameter interpretation diagram, defining degree of venous system condition as normal, equivocal or pathological. Target sportsmen were examined in siting position with physical loading pedis. Sportsmen lower extremity vein light transducing change registration associated with the degree of vessel filling was studied by digital photopletismography . The study results showed that vein restoration time (VRT) in football players is two times minor to compare to the one of wrestlers, while venous pump (VP) function is about 1.5 times higher in footballers than in wrestlers. Degree of lower extremity venous system condition according to parameter interpretation diagram program showed normal values only in few cases. Slight deviations were observed only in individuals with recent trauma. Further examination after the appropriate treatment revealed normal values in traumatic subjects. The search also showed that digital photopletismography appears to be effective, simple and financialy available diagnostic method, which should be more frequently applied in lower extremity vein function examinations among sportmen of different kinds as well as in estimation of recovery therapy effectiveness in post-trauma period.